The history of the Philippines - Nadeau, Kathleen M. 1952- (Westport, Connecticut Greenwood Press, 2008)
Provides a comprehensive account of the Philippines and its struggle to discover a national identity.
Southeast Asian prehistory and the Philippines -- Spanish colonization (1521-1896) -- The Philippine revolution (1896-1902) -- American colonization (1899-1946) -- Philippine independence (post-World War II) -- The Marcos regime (1965-1986) -- The Philippines after Marcos.
Keywords: Electronic books; Philippines -- History; Philippines -- Politics and government; Philippines -- Economic conditions; Philippines -- Social conditions